The impacts of working space on productivity of young freelancers in the creative industries in the Czech Republic - Nguyen, Ngoc Mai (2023)
Working from home has gained popularity across the globe, especially since the Covid-19 pandemic happened. Nonetheless, with the advancement of technology, the home office has been a popular choice for self-employed individuals in the creative industries for a long time. Therefore, the purpose of this thesis was to investigate how working environments, particularly home offices, affect the productivity of freelancers in the Czech Republic's creative industries. The study was based on a thorough review of the literature and qualitative research that took place in the form of semi-structured interviews with 12 independent creatives who occasionally work from home. The results demonstrate that the working environment significantly impacts the self-perceived productivity of independent creatives. Different aspects of a home office, such as comfort, ergonomics, lighting, windows, outside views, indoor plants, noise, appearance, and organization, can influence how productive a freelancer is. Furthermore, numerous distractions come with working from home because it is also a space for personal life; thus, it is essential to establish boundaries. Some suggestions are made to help independent creatives maintain their concentration and productivity while working from home.